Exploring Registered Psychiatric Nurses' Responses towards Service Users with a Diagnosis of Borderline Personality Disorder - Bridget McGrath; Maura Dowling (Hindawi Limited, 2012)
This study explored registered psychiatric nurses' (RPNs') interactions and level of empathy towards service users with a diagnosis of borderline personality disorder (BPD). A qualitative approach was used, and 17 RPNs were interviewed using a semistructured interview schedule incorporating the "staff-patient interaction response scale" (SPIRS). Four themes emerged following data analysis: "challenging and difficult," "manipulative, destructive and threatening behaviour," "preying on the vulnerable resulting in splitting staff and other service users," and "boundaries and structure." Additionally, low levels of empathy were evident in the majority of participants' responses to the SPIRS. The findings provide further insight on nurses' empathy responses and views on caring for service users with BPD and further evidence for the need for training and education for nurses in the care of service users diagnosed with BPD.